In-situ forming drug-delivery systems for periodontal treatment: current knowledge and perspectives. (4th October 2021) - Dubar, Marie; Lizambard, Martin; Delcourt-Debruyne, Elisabeth; Batool, Fareeha; Huck, Olivier; Siepmann, Florence; Agossa, Kevimy
Abstract: Several chemical compounds are considered to be promising as adjuvants in the treatment of periodontitis. Antimicrobials, anti-inflammatory drugs or, more recently, pro-regenerative or antioxidant molecules have shown a very interesting potential to improve the outcomes of mechanical biofilm removal and promote the healing of the damaged tissues. However, their clinical effect is often limited by the challenge of achieving effective and prolonged drug delivery within the periodontal lesion, while limiting the risk of toxicity. In-situ forming implants (ISFI) are 'implantable' drug-delivery systems that have gained considerable attention over the last few decades due to their multiple biomedical applications. They are liquids that, when injected at the site to be treated, form a semi-solid or solid dosage form that provides safe and locally controlled drug release. This review discusses current data and future prospects for the use of ISFI in periodontal treatment.